The complete mitochondrial genome of the lychee stinkbug Mattiphus splendidus (Hemiptera: Tessaratomidae) - Xu, Shiwen (Mitochondrial DNA B Resour, 2019)
The lychee stinkbug Mattiphus splendidus is an important pest which mainly distributed in southern China. In this study, we sequenced and described the complete mitochondrial genome (mitogenome) of M. splendidus, which is the first record in the genus Mattiphus. This mitogenome is 15,973 bp long and comprises of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a control region. Gene order is identical to that of the putative ancestral arrangement of insects. All protein-coding genes initiate with ATN, expect ND1and COI use GTG or TTG as start codons and terminate with TAG or TAA, expect COI and COIII use TA or a single T residue as the stop codon. All tRNAs, ranging from 62 to 74 bp, can be folded into typical clover-leaf structure expect for tRNA(Ser(GCU)) and tRNA(Val). The control region is 1,357 bp long with 73.5% A + T content. The phylogenetic analysis supports the monophyly of Tessaratomidae and the sister relationship between M. splendidus and Eusthenes cupreus.